Analysis Of Tuaks As Raw Material Of Juruh Ental Sugar For Tourism Products In Les Village, Tejakula District - Nyoman Danendra Putra; Luh Oka Puji Apsari; Ngurah Artama; Anak Agung Gede Mahendra (Tourism Department, State Polytechnic of Banyuwangi, 2024)
Tuak is the basic ingredient of Juruh Sugar where Juruh Sugar is a product that comes from Les Village, Tejakula District. The aim of this research is to explain how to produce quality Tuak as a basic ingredient for making Juruh Sugar during the summer and rainy season, describe the traditional process of making Juruh Sugar as a Tourism Product and explain the promotion of Juruh Sugar. The type of research applied is qualitative research with a case study approach and its application uses 2 theories, namely production theory by Surur, M (2021) and promotion mix theory by Tjiptono. Determining informants was carried out based on purposive sampling techniques and determining data collection methods through interviews, observation and document study. The results of the research show that during the rainy season the palm wine produced contains more water content than during the summer season which contains more sugar content. Tuak farmers work around this by covering the palm wine with plastic, sacks or thick leaves so that rain water does not enter. into palm wine. Juruh Sugar is liquid sugar made from sweet Tuak, where the making of Juruh Sugar still uses traditional methods, the Juruh Sugar production process also pays attention to natural factors, labor factors and capital in the production process. Juruh Sugar products have also been promoted through social media, advertising, events and MSME exhibitions.